1993
DOI: 10.1042/bst021220s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a milk fat globule membrane fraction on cultured mouse mammary cells

Abstract: During lactation mammary cell number is regulated by an intramammary mechanism sensitive to the frequency of milking. Thus, a unilateral increase in cell number is elicited when one gland of lactating goats is milked thrice instead of twice daily [l]. The local increase in cell number i s associated with a higher rate of DNA synthesis in the thrice-milked gland [l]. However, it is also possible that the response is due in part to a reduction in the loss of mammary secretory cells at this stage of lactation. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…3) In the milk fat route, milk fat globules are extruded from the apex of the secretory cell surrounded by membrane (milk-fat-globule membrane); some cytoplasm is sometimes included (126). Examples are milk fat, lipidsoluble hormones and drugs, some unknown growth factors (in milk-fat-globule membrane) (244), and the product of the ob gene, leptin (214).…”
Section: )mentioning
confidence: 99%
“…3) In the milk fat route, milk fat globules are extruded from the apex of the secretory cell surrounded by membrane (milk-fat-globule membrane); some cytoplasm is sometimes included (126). Examples are milk fat, lipidsoluble hormones and drugs, some unknown growth factors (in milk-fat-globule membrane) (244), and the product of the ob gene, leptin (214).…”
Section: )mentioning
confidence: 99%
“…It must be inferred that the amount of FIL in the circulation was insufficient to affect the mammary cells or that FIL works through the apical rather than the basolateral membrane of the secretory cell. Similarly, MFGM, which contains a substance that inhibits mammary cell proliferation (see Brandt, Pepperle, Otto, Kraft, Bohmer & Grosse, 1988) and a substance that increases the longevity of mammary cells (Wendrinska et al 1993), had no apparent effect. Heesom, Souza, Ilic & Williamson (1992) have suggested that medium-chain fatty acids in milk could provide a local (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the milk fat globules were fractionated into their components to determine whether a specific inhibitory component could be identified. Milk fat globule membranes (MFGM) were prepared as described by Jarasch, Bruder, Keenan & Franke (1977) and Wendrinska, Addey, Orange, Boddy, Hendry & Wilde (1993). MFGM from 2 ml of milk was injected after resuspension in 0 2 ml 0 154 M NaCl.…”
Section: Introductionmentioning
confidence: 99%